2006
DOI: 10.1074/jbc.m601545200
|View full text |Cite
|
Sign up to set email alerts
|

Global Translational Responses to Oxidative Stress Impact upon Multiple Levels of Protein Synthesis

Abstract: Global inhibition of protein synthesis is a common response to stress conditions. We have analyzed the regulation of protein synthesis in response to oxidative stress induced by exposure to H 2 O 2 in the yeast Saccharomyces cerevisiae. Our data show that H 2 O 2 causes an inhibition of translation initiation dependent on the Gcn2 protein kinase, which phosphorylates the ␣-subunit of eukaryotic initiation factor-2. Additionally, our data indicate that translation is regulated in a Gcn2-independent manner becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

43
407
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(460 citation statements)
references
References 55 publications
43
407
1
3
Order By: Relevance
“…This finding is in excellent agreement with recent studies in yeast cells, in which the authors reported the inhibition of protein translation during peroxide stress, caused in part by defects in protein elongation and/or termination (31). By stalling elongating ribosomes, cells not only prevent formation of erroneous proteins but increase their ability to rapidly resume protein synthesis upon return to non-stress conditions (31). As such, down-regulation of protein translation during oxidative stress might provide an adaptive mechanism to increase oxidative stress resistance of cells (32).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is in excellent agreement with recent studies in yeast cells, in which the authors reported the inhibition of protein translation during peroxide stress, caused in part by defects in protein elongation and/or termination (31). By stalling elongating ribosomes, cells not only prevent formation of erroneous proteins but increase their ability to rapidly resume protein synthesis upon return to non-stress conditions (31). As such, down-regulation of protein translation during oxidative stress might provide an adaptive mechanism to increase oxidative stress resistance of cells (32).…”
Section: Resultssupporting
confidence: 93%
“…We also detected oxidation-sensitive cysteines in the elongation factors Eft1 and Eft2, which previously have been characterized to be redox-sensitive (17,20). This finding is in excellent agreement with recent studies in yeast cells, in which the authors reported the inhibition of protein translation during peroxide stress, caused in part by defects in protein elongation and/or termination (31). By stalling elongating ribosomes, cells not only prevent formation of erroneous proteins but increase their ability to rapidly resume protein synthesis upon return to non-stress conditions (31).…”
Section: Resultssupporting
confidence: 91%
“…translation initiation (Ashe et al 2000). This approach allows the detection of an effect on ribosomal transit without the added complication of de novo translation initiation (Shenton et al 2006). WT and gua1-G388D cells were grown at 28°for 2 or 5 min after glucose withdrawal, cycloheximide was added for 5 min to fix the positions of elongating ribosomes, and the P/M ratios were quantified from polysome profiles.…”
Section: Resultsmentioning
confidence: 99%
“…Clusters 6 and 7 (1391 genes) exhibit a large decrease of RA accompanied by TR down-regulation, which is more dramatic in the genes of cluster 6. The two clusters include most of the genes implicated in ribosome structure and biogenesis (RP and rRNA-processing enzymes), and this reflects the inhibition of protein synthesis after application of oxidative stress (21). However, TR inhibition alone is not sufficient to explain the decrease in RA in clusters 6 and 7 genes.…”
Section: Mrna Synthesis and Decay During The Yeast Oxidative Responsementioning
confidence: 99%
“…This proteome pattern, although limited to about 20% of all expressed proteins in yeast cells, approximately parallels the transcriptome pattern (1), which indicates that the oxidative stress response mainly occurs through regulation of mRNA level. However, recent studies demonstrate that inhibition of protein synthesis occurring after an oxidative stress is not only caused by transcriptional down-regulation of the translation machinery but also by inhibition of translation initiation due to dissociation of ribosomes from mRNA and a slower rate of ribosomal runoff along mRNA molecules (20,21). This illustrates the importance of the post-transcriptional level of regulation (22), which may also involve the regulation of mRNA translation efficiency by 3Ј-AU-rich elements, as is the case of the MFA2 mRNA in S. cerevisiae (23).…”
mentioning
confidence: 99%